A pesquisa e a atividade docente - Moura de Mello, Luciano; Tibulo, Cleiton; Cavichioli Braida, Fabrícia; Magali Holz, Sheila; Buske, Rodrigo; Dias, Guilherme (Revista Científica Schola, 2017)
Editorial